Targeting and treatment of glioblastomas with human mesenchymal stem cells carrying ferrociphenol lipid nanocapsules - Clavreul A (Dove Medical Press, 2015)
Anne Clavreul,1 Angélique Montagu,2 Anne-Laure Lainé,2 Clément Tétaud,2 Nolwenn Lautram,2 Florence Franconi,3 Catherine Passirani,2 Anne Vessières,4 Claudia N Montero-Menei,2 Philippe Menei1 1Département de Neurochirurgie, Centre Hospitalier Universitaire, Angers, France; 2INSERM UMR-S 1066, Université d’Angers, LUNAM Université, Angers, France; 3CIFAB-PRIMEX, Université d’Angers, LUNAM Université, Angers, France; 4CNRS-UMR 7223, ENSCP, Paris, France Abstract: Recently developed drug delivery nanosystems, such as lipid nanocapsules (LNCs), hold great promise for the treatment of glioblastomas (GBs). In this study, we used a subpopulation of human mesenchymal stem cells, “marrow-isolated adult multilineage inducible” (MIAMI) cells, which have endogenous tumor-homing activity, to deliver LNCs containing an organometallic complex (ferrociphenol or Fc-diOH), in the orthotopic U87MG GB model. We determined the optimal dose of Fc-diOH-LNCs that can be carried by MIAMI cells and compared the efficacy of Fc-diOH-LNC-loaded MIAMI cells with that of the free-standing Fc-diOH-LNC system. We showed that MIAMI cells entrapped an optimal dose of about 20 pg Fc-diOH per cell, with no effect on cell viability or migration capacity. The survival of U87MG-bearing mice was longer after the intratumoral injection of Fc-diOH-LNC-loaded MIAMI cells than after the injection of Fc-diOH-LNCs alone. The greater effect of the Fc-diOH-LNC-loaded MIAMI cells may be accounted for by their peritumoral distribution and a longer residence time of the drug within the tumor. These results confirm the potential of combinations of stem cell therapy and nanotechnology to improve the local tissue distribution of anticancer drugs in GB.Keywords: glioblastoma, mesenchymal stem cells, nanoparticle, drug delivery, targeting